Plan de negocios para constituir una academia de Taekwondo en la Urbanizacion Villa Club cantón Daule - Mosquera Olivares, Jhair Enrique (2024)
The project is based on the creation of a business plan to establish a Taekwondo academy in the Villa Club urbanization of the Daule canton. As it is about self-defense, it attracts the attention of those who want to learn this sport and as there is no academy with these characteristics in the Villa Club area, it becomes even more attractive for those who want to practice it..........